Lithuanian Social Entrepreneurs’ Experiences of Evaluating the Impact of Their Social Businesses - Pušinaitė-Gelgotė, Rasa; Pučėtaitė, Raminta; Novelskaitė, Aurelija (Information & Media, 2019)
This paper raises research questions on how social business representatives assess the impact of their social businesses and what methods they use to evaluate or measure it. The findings of data analysis of the interviews with 20 social entrepreneurs in Lithuania indicate that social entrepreneurs just begin to measure impact and do not always distinguish it from outcomes and outputs. This can also be influenced by impact measurement methods/tools, which are publicly available for social entrepreneurs or provided by funding organizations. Social entrepreneurs acknowledge that they must create and evaluate this impact, but research findings indicate that they distinguish more reasons not to do that. Impact evaluation is more explicitly revealed when discussing internal (consumers, employees) rather than external stakeholders. Some social entrepreneurs understand the need to evaluate their activities in monetary terms, but they do not do it, which is explained by the early development stage of social businesses in Lithuania. Moreover, social entrepreneurs do not have experience in measuring impact from a multidimensional perspective, i.e., including the social, environmental, cultural, and economic dimensions, and it seems that the necessity of doing this has not come to their awareness yet. The article is concluded with recommendations for strengthening social entrepreneurs’ capabilities in impact evaluation.